2015
DOI: 10.1177/1534735415596569
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Su Fu’ning Lotion’s Inhibitory Effects on Bladder Cancer Cells In Vitro and In Vivo by Intravesical Instillation

Abstract: Background. Bladder cancer is a common malignant tumor with a very high recurrence rate after surgery. Intravesical instillation can help clear up the residual tumor cells after surgery and thereby reduce the recurrence rate. Objective. To establish a bladder tumor transplantation animal model and to evaluate the inhibitory effects of a novel perfusate, Su Fu'ning Lotion (SFN), on bladder tumor. Methods. SFN was compared with several commonly used chemotherapy drugs, including mitomycin (MMC) and pirarubicin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The clinical efficacy of pirarubicin and MMC is well established; for example, a recent meta-analysis concluded that intravesical administration of pirarubicin and MMC after TURBT was associated with a reduced tumor recurrence (hazard ratios of 0.31 and 0.40, respectively) and prolonged recurrence-free survival (hazard ratios of 0.31 and 0.44, respectively) 5 . Our finding that pirarubicin and MMC inhibited the proliferation of cultured BIU-87 cells is consistent with clinical observations and in agreement with other in vitro studies in bladder cancer cell lines 20 – 22 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The clinical efficacy of pirarubicin and MMC is well established; for example, a recent meta-analysis concluded that intravesical administration of pirarubicin and MMC after TURBT was associated with a reduced tumor recurrence (hazard ratios of 0.31 and 0.40, respectively) and prolonged recurrence-free survival (hazard ratios of 0.31 and 0.44, respectively) 5 . Our finding that pirarubicin and MMC inhibited the proliferation of cultured BIU-87 cells is consistent with clinical observations and in agreement with other in vitro studies in bladder cancer cell lines 20 – 22 .…”
Section: Discussionsupporting
confidence: 93%
“…SFN is an extract from Sappan wood ( Caesalpinia sappan L.) that is used as a traditional Chinese medicine. SFN can inhibit the proliferation of three different bladder cancer cell lines (BIU-87, T24 and BTT cells) as well as reduce bladder wet weight and prolong survival in mice with bladder cancer xenografts (using T24 or BTT cells) 20 . Although the mechanism by which SFN exerts an anticancer effect remains to be elucidated, our in vitro observations agree well with this previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current treatment modalities for NMIBC are mainly transurethral bladder tumor electrosurgery and postoperative gemcitabine intravesical infusion chemotherapy, which can cause damage to the organism for a long time after surgery, leading to bladder irritation, intestinal discomfort, and other symptoms, and some patients may experience recurrence or even accelerate the progression of NMIBC patients after surgery [ 14 ]. To solve such problems, many scholars have proposed the concept of treating bladder cancer by combining traditional Chinese medicine with postoperative perfusion, which has achieved certain clinical effects [ 15 17 ]. The application of Xiaozheng decoction, combined with gemcitabine bladder perfusion to prevent recurrence and adverse reactions after NMIBC, achieved relatively satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
“…The bladder is a hollow organ, and bladder cancer is commonly located on the surface of its mucosal lining ( Batista et al, 2020 ). During treatment, diluted anti-tumor drugs are perfused into the bladder to make direct contact with the cancer cells in the mucosal lining ( Ren et al, 2016 ; Bao et al, 2020 ), without the need to administer the drugs through vascular injection or other means. Therefore, bladder cancer is suitable for magnetic drug targeting therapy without the formation of thrombus blockages and other problems.…”
Section: Drug Delivery and Mpi Experimentsmentioning
confidence: 99%